CIRCULAR ECONOMY AND ITS BARRIERS TO IMPLEMENTATION IN THE CONSTRUCTION SECTOR: GNP 2024 - Milović, Tiana; Laban, Mirjana; Starčev-Ćurčin, Anka; Bulatović, Vesna (Journal of Applied Engineering Science, 2024)
The concept of circular economy has become an important topic during the last decade, because it offers a systems solution framework that creates a closed-loop system to minimize waste and maximize resource efficiency in order to achieve a better balance and harmony between economy, environment and society. The construction industry has significant potential to apply a circular economy model since this industry is responsible for considerable global natural resource extraction and solid waste production. Worldwide, more than 10 billion tons of construction and demolition waste are produced annually, while the demolition alone is responsible for 50% of all waste produced by the building sector. In Serbia, the sectors of agriculture, forestry and fishing, mining, manufacturing, electricity, gas and steam supply, water supply and wastewater management, construction and service activities generated 56.3 million tons of waste just during 2020. Although 80% of construction waste can be recycled according to the Agency for Environmental Protection reports the waste recycling has not yet been established in Serbia. On the other hand, Serbia adopted the Roadmap for Circular Economy in Serbia, the Law of Waste Management, the Regulation on the Manner and Procedure of Waste Management from Construction and Demolition, and accepted the conditions of the European Union for linking the European Green Deal with the strategic development of the region by signing the Green Agenda for the Western Balkans. This paper provides a brief literature review that introduces the circular economy by presenting its origin, definition and principles as well as the barriers (five categories: technological, economic, socio-cultural, institutional and regulatory) to its wider adoption in the construction sector.